ARTIFICIAL INTELLIGENCE IN BUSINESS ACCOUNTING (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article explores the transformative role of artificial intelligence (AI) in the field of business accounting in Uzbekistan. It discusses the ways AI technologies are enhancing the efficiency, accuracy, and transparency of accounting processes for companies in the region. The study examines key applications, including automated data entry, predictive analytics, and real-time financial monitoring, which help reduce human error, streamline operations, and provide valuable insights for strategic decision-making. Additionally, the article addresses the unique challenges faced by Uzbekistan’s accounting sector in adopting AI, such as regulatory considerations, digital infrastructure, and workforce readiness. By highlighting the benefits and potential barriers, the article offers insights into how Uzbek companies can leverage AI to improve financial management and gain a competitive edge in a globalized market.